Comparative evaluation of platelet-rich fibrin with demineralized freeze-dried bone allograft in periodontal infrabony defects: A randomized controlled clinical study - Monali Shah; Jay Patel; Deepak Dave; Sujal Shah (Wolters Kluwer Medknow Publications, 2015)
Introduction: Several bone graft materials have been used in the treatment of infrabony defects. Demineralized freeze-dried bone allograft (DFDBA) has been histologically proven to be the material of choice for regeneration. However, platelet-rich fibrin (PRF) has been said to have several properties that aid in healing and regeneration. Hence, this study focuses on the regenerative capacity of PRF when compared with DFDBA. Materials and Methods: A total of 40 sites with intrabony defects were selected and were assigned to the test group (open flap debridement [OFD] and PRF, n = 20) and the control group (OFD + DFDBA, n = 20). At the test sites, two PRF plugs were placed in the intrabony defect after debridement of the site and flap was sutured in place. The parameters measured were probing depth (PD), relative attachment level (RAL), and gingival marginal level (GML). These parameters were measured just before surgery (baseline) and at 6 months postsurgery. The changes in PD, RAL, and GML were analyzed at baseline and postsurgically after 6 months in each group with paired t-test and between the two groups with unpaired t-test. Results: The mean reduction in PD after 6 months in the test PRF group is 3.67 ± 1.48 mm where in control DFDBA group is 3.70 ± 1.78 mm. Gain in RAL in the test PRF group is 2.97 ± 1.42 mm where in control DFDBA group, it is 2.97 ± 1.54 mm. Gingival margin migrated apically in the test PRF group by 0.43 ± 1.31 mm where in control DFDBA group by 0.72 ± 2.3 mm. It was seen that the differences in terms of PD (P = 0.96), RAL (P = 1.00) and GML (P = 0.62) were not significant. Conclusion: Platelet-rich fibrin has shown significant results after 6 months, which is comparable to DFDBA for periodontal regeneration in terms of clinical parameters. Hence, it can be used in the treatment of intrabony defects.